An evaluation of the flood diversion project due to extreme rainfall event in Taipei City. (October 2019) - Wu, S; Jang, J; Wu, T; Lin, J; Li, B
Abstract: Governments in Taiwan attach great importance to flood control and disaster mitigation project. Good simulation and estimation in advance are the key point to prevent damages and losses caused by flood disasters. The main objective of this study is to investigate the effectiveness of the Drainage and Flood Control System in Wenshan District completed by the Taipei City Government. SWMM (Storm Water Management Model, US Environmental Protection Agency), a dynamic rainfall-runoff simulation computer program designed for runoff water quantity and quality of single or continuous events in urban areas, is utilized to perform the simulation and analysis in this study. Based on known basic data of facilities such as pipelines, channels, and water storage system, and by setting data related to typhoons and heavy rains from the past records, the runoff at a certain period in each area and the flow and depth in each pipeline are estimated and simulated. By comparing the simulation results with the results before the construction, we can evaluate the effectiveness on the Drainage and Flood diversion system and predict the possible defects. Accordingly, the engineering plan can be modified promptly before the construction to enhance the effect of flood control and disaster mitigation.